Building Subnational Debt Markets in Developing and Transition Economies : A Framework for Analysis, Policy Reform, and Assistance Strategy - Noel, Michel (World Bank, Washington, DC, 2014)
Subnational debt markets can be a powerful force in a country's development. Through delegated monitoring by financial intermediaries and through debt placed directly with investors, subnational debt markets account for about 5 percent of GDP in Argentina and Brazil. But they remain embryonic in most developing and transition economies. To resolve a potential clash between the increased financing needs of subnational entities and the limited development of domestic subnational debt markets, it is critical to support the orderly, efficient emergence of such debt markets. As a framework for policy reform, the following steps (mirroring typical weaknesses) are prerequisites for developing a country's subnational debt market: reducing moral hazard, improving market transparency, strengthening market governance, establishing a level playing field, and developing local capacity for accounting, budgeting, and financial management. In countries where the government shows a clear commitment to market development, says the author, the World Bank should support the framework needed for policy-based operations that establish hard budget constraints. In doing so, the Bank should concentrate on 1) supporting national and local capacity building in those areas essential for developing a subnational debt market; and 2) financing specific subnational projects with strictly nonrecourse loans. At the same time, the Bank should offer a variety of lending and guarantee instruments that encourage private financing for investments by subnational entities-including, for example, equity participation in (or lines of credit or partial credit guarantees to) financial intermediaries specializing in subnational investment finance or in funds for financing local infrastructure.